The earth : its materials, process, and history : essentials of earth science - Marquez, Edanjarlo J.; Gabo, Astrid Korina S. (Quezon City : St. Bernadette Publishing House Corporation, 2015)
"Earth Science encompasses fields of study concerned with understanding the Earth ; also extending to other bodies in the Solar System. Covering a wide rage of topics, Earth Science includes astronomy, meteorology, oceanography, and geology."
English text.
Keywords: Earth science